Akurasi Penilaian Aset Biologis : Sebuah Pendekatan Studi Kasus Eksploratif - Nuraini, Intan; Syah, Sultan (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2025)
Abstract. Accuracy Of Biological Asset Assessment: A Case Study Approach.The aim of this research is to analyze the accuracy of biological asset assessment using a case study approach at PT Bukit Palem. This research uses a descriptive qualitative method with an explanatory case study approach as an analysis tool. The types of data used are primary and secondary data. The results of this research show that the assessment of PT Bukit Palem's biological assets is in accordance with PSAK 69 by utilizing an accuracy tool for the number of asset suitability using drones in the asset measurement section. This research also involves a significant contribution in improving the management of biological assets at PT Bukit Palem.